BIOM-10. PRECLINICAL PLATFORM FOR THE IDENTIFICATION OF DEUTERIUM MAGNETIC RESONANCE SPECTROSCOPY-BASED BIOMARKERS OF BRAIN TUMOR METABOLISM. (12th November 2021) - Batsios, Georgios; Tran, Meryssa; Taglang, Céline; Gillespie, Anne Marie; Ronen, Sabrina; Costello, Joseph; Viswanath, Pavithra
Abstract: Metabolic reprogramming is a fundamental hallmark of cancer, which can be exploited for non-invasive tumor imaging. Deuterium magnetic resonance spectroscopy ( 2 H-MRS) recently emerged as a novel, translational method of interrogating flux from 2 H-labeled substrates to metabolic products. However, to date, preclinical studies have been performed in vivo, an endeavor which suffers from low-throughput and potential wastage of animal life, especially when considering studies of treatment response. Developing in vitro assays for monitoring metabolism of 2 H-labeled substrates will enhance throughput, lead to the rapid evaluation of new 2 H-based probes and enable identification of treatment response biomarkers, thereby allowing the best 2 H-based probes to be translated for further in vivo assessment. The goal of this study was to develop a preclinical cell-based platform for quantifying metabolism of 2 H-labeled probes in brain tumor models. Since the Warburg effect, which is characterized by elevated glycolytic production of lactate, is a metabolic phenotype of cancer, including brain tumors, we examined metabolism of 2 H-glucose or 2 H-pyruvate in patient-derived glioblastoma (GBM6) and oligodendroglioma (BT88) cells and compared to normal human astrocytes (NHACONTROL ). Following incubation in media containing [6, 6'- 2 H]glucose or [U- 2 H]pyruvate, 2 H-MR spectra obtained from live cell suspensions showed elevated 2 H-lactate production in GBM6 and BT88 cells relative to NHACONTROL . Importantly, 2 H-lactate production from [6, 6'- 2 H]glucose or from [U- 2 H]pyruvate was reduced in GBM6 or BT88 cells subjected to irradiation and temozolomide, which is standard of care for glioma patients, pointing to the utility of this method for detecting response to therapy. Collectively, we have, for the first time, demonstrated the ability to quantify metabolism of 2 H-MRS probes in live cell suspensions and validated the utility of our assay for differentiating tumor from normal cells and assessing response to therapy. Our studies will expedite the identification of novel 2 H-MRS probes for imaging brain tumors and potentially other types of cancer.